New polyether diols as flame retardants for polyurethane: Derivatives of epoxy‐functionalized phosphonates and phosphates. (16th July 2017) - Byard, Benjamin; Wang, Kui; Morgan, Alexander; Benin, Vladimir
Summary: Phosphorus‐containing epoxides were used to generate several oligomeric polyether diols, which were in turn utilized in the preparation of model polyurethane (PU) samples, either as comonomers in the polymerization ( Prep samples) or solvent blended into a priori prepared PU ( Blend samples). The resultant samples were evaluated for heat release reduction potential using microcombustion calorimetry. Several variables were investigated in the oligomerization of the original epoxides, such as presence of initiator, epoxide comonomer, and solvent. The oligomer mixtures were thoroughly characterized, using NMR, mass spectrometry (MS), elemental analysis, and viscosity measurements. The final PU Prep samples were carefully analyzed to demonstrate and evaluate the degree of chemical incorporation of the polyether diols into the PU main chain. Results from the heat release studies demonstrated that incorporation of the phosphorus‐containing diol did lower flammability, but the structure of the original epoxide, as well as the oligoimerization conditions, had an effect on heat release reduction. The results are complex and require further study, but the phosphonate‐based materials showed greater heat release reduction potential, both in the form of Prep and Blend samples, especially in one case of a Blend sample, where a notable amount of intumescent char was formed.